RISK ANALYSIS OF INVESTMENT A NEW FACTORY WITH MONTE CARLO SIMULATION - I Ketut Gunarta (Universitas Gunadarma, 2009)
A case study of an investment in developing a new factory was conductedone of critical factors which are concern in foreign investment evaluation,exchange rate of US to IDR (Rupiah). The exchange rate’s fluctuationeffect on the financial engineering project and also the firm performance,investment was funded by export debt. The exchange rate risk wasCarlo simulation model.Key Words: Risk, Monte Carlo Simulation, Financial Indicators.